Mechanical and durability studies of high performance concrete (HPC) with nano-silica. (2022) - Vivek, D.; Elango, K.S.; Gokul Prasath, K.; Ashik Saran, V.; Ajeeth Divine Chakaravarthy, V.B.; Abimanyu, S.
Abstract: Concrete is the commonly used building material everywhere but it's maintenance in severe exposure areas are really challenging for engineers. In order to attain better performance throughout its lifetime without detrimental to its quality, it is recommended to use HPC. HPC is mostly preferable for its durability and strength which is suiTable for long term structures and heavily loaded bridges. In this project, a mix ratio is arrived for high graded concrete and an optimum percentage of silica fume (SF) is added as pozzolanic reactor. Nano silica (nS) is a suiTable cementitious material for packing the voids in concrete and added in various proportions to improve the density and impermeability. Adding up of nS and SF may reduce the ease of work to fulfil the needs of fresh concrete super plasticizer (CONPLAST SP430 G8) is used. The durability and mechanical properties of HPC with varying parameters was studied. The optimum level of ns in HPC was found by considering the relevant tests.